Concepts of Some Indigenous Pottery Decorative Techniques in Northern Ghana - Iddrisu, Yussif; Adu-Gyamfi, Vesta E. (European Scientific Journal, ESJ, 2017)
The aim of this paper was to identify some concepts of indigenous pottery within the three northern regions of Ghana. As a result, emphasis was given to the identification of some concepts of indigenous pottery in northern Ghana. The descriptive approach of the qualitative research methodology was used. Interview and observation methods were employed as the data collection processes to ascertain reasons why they engage in pottery decoration and the concepts behind them. The data was subjected to comparative analyses and the indications were that, the people of northern Ghana make interesting forms of decorative techniques which comes with an authentic concepts. The study revealed that, there are eight identified indigenous pottery decorative techniques which included; incision, impression, stainning, blasting, smooking, perfforation, macrame and modeling. With these techniques the researchers realised that there are some basic concepts behind each and every decorative techniques found on the indigenous pottery. These included; convertions of red ferric ironoxide to black ferric ironoxide, reduction of friction, restriction purposes and movement and handling purposes.